Análise das pegadas fósseis de tetrápodes do Permiano Superior da Bacia do Paraná - Silva, Rafael Costa da (2004)
The objectives of this dissertation are to identify, describe and interpret the fossil footprints of the Permian Paleofaunas tetrapods and to analyze the characteristics of the environments where they were produced in Irati, Rio do Rasto and Corumbataí formations. The material comprises six samples with ichnofossils from Rio do Rasto Formation (São Jerônimo da Serra, PR) and others 25 from lrati Formation (Guapirama, PR, Portelândia e Perolândia, GO), besides 21 photographies and two plastic maps drew on the footprints from Corumbataí Formation (Taguar, SP). The ichnofossils from lrati Formation were identified as lchnogen. nov. A ichnosp. nov. A and atributted to mesosaurid reptiles. They were originated under the action of the storm waves in a tidal flat depositional system and it would have been produced during the swimming next to the bottom. The footprints from Corumbataí Formation were identified as Tridactylichnium ichnosp. And atributted to the archosauromorphs, probably Euparkeriidae. The trackmaker were semibipeds with functionally tridactyl hands and feet when walking and running. Ln the Rio do Rasto Formation occurs two kinds of footprints, identified as Rhynchosauroides ichnosp. nov. A and Dicynodontipus ichnosp. Atributed respectively to Lepidossauromorpha and Therapsida. These ichnofossils were produced in the border of a low lake after the entrance of debris flows under a small edge of water. R. ichnosp. nov. A corresponds to the first ichnospecies of this ichnogenus described at the South Hemisfer. The rock layers where they occur were originated in the lower triassic or during the permotriassic transition. The footprints of the Passa Dois Group represent natural and homogene animais populations, being that three (Tridacty/ichnium ichnosp., Rhynchosauroides ichnosp. nov. A e Dicynodontipus ichnosp.) of the four ichnotaxa correspond to animais without osteologic register in this geologic unit.